The Problems of Building Construction in Manacapuru-AM: The Correnteza and Terra Preta Neighborhoods (Global Journal of Human-Social Science, 2024)
In Manacapuru the region of Solim es River is one lowland which is formed by fragile soil Construction in these areas can be affected by several difficulties such as building instability due to the force of waters during floods and rotting of pillars Other aspects of the phenomena of nature such as floods rain and moisture require high maintenance expenses and a short life cycle in wooden buildings These factors make this population more vulnerable as well as the risk of losing their home furniture and personal property This region is undergoing significant transformations so many parts of the territory are at risk of landslides and soil erosion The method consisted of a case study website visits production of maps with QGIS and Google Earth redesign of areas vulnerable to flooding and geological risk The analysis concludes in the neighborhood Terra Preta the possibility of geological risk is high but contained in the low-lying areas and the stream The Correnteza neighborhood presents a greater risk of flooding because it has two influences from the Solim es River and the sandy surface river Areal Most of the buildings are on wooden stilts and there are more houses with instability and maintenance issues
Keywords: socio-environmental risks; geological risks; landslide risks; floodplain areas